Alkaline-earth metal methyl sulfonate compound and crystal, preparation method and application thereof

The new alkaline earth metal methylsulfonate compounds and their crystals were prepared through hydrothermal reaction, which solved the problem of fewer types of existing methylsulfonate compounds, and realized the preparation of compounds and crystals suitable for different fields, with stable physical and chemical properties and low-cost preparation methods.

CN119874570AActive Publication Date: 2025-04-25TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411853164.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

There are fewer types of methylsulfonate compounds and it is difficult to apply to different fields.

Method used

A new alkaline earth metal methylsulfonate compound with the formula My(SO3CH3)X·nH2O and its crystals were prepared by mixing the compound containing the M element, an X element, and a compound containing a methylsulfonate group through a hydrothermal reaction.

Benefits of technology

The prepared compounds and crystals have stable physical and chemical properties, and are suitable for use in the fields of optical materials and chemical raw materials, and are simple in preparation and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874570A_ABST
    Figure CN119874570A_ABST
Patent Text Reader

Abstract

The invention discloses an alkaline earth metal methyl sulfonate compound as well as a crystal and application thereof, the chemical formula of the crystal is My (SO3CH3) X.nH2O, the crystal is crystallized in a centrosymmetric space group P21 / n, Pnma, P4 / nmm, P4 / nmm, P21 / n, Pbca or # imgabs0 #, and the crystal is structurally characterized in that alkaline earth metal atoms M and SO3CH3 are connected through shared O atoms to form a two-dimensional infinite alkaline earth metal M-SO3CH3 layer, and halogen is arranged between the two layers. Due to the introduction of halogen, the system of the metal methyl sulfonate is improved. Meanwhile, the crystal of the system does not absorb moisture, is stable in air and has good physical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical industry and crystal materials, and specifically relates to an alkaline earth metal methane sulfonate compound and its crystal, a preparation method and application in chemical raw materials and the like. Background Art

[0002] Methanesulfonate compounds have gradually become a hot topic of research in recent years due to their unique molecular structure and chemical stability. Methanesulfonate crystals have a wide light transmittance range and good thermal stability, and are easy to grow by solution method, suitable for large-scale production. Methanesulfonic acid (CH4SO3) is a strong acid with a unique molecular structure and chemical stability. The sulfonic acid group (-SO3H) in the methanesulfonic acid molecule has strong polarity and hydrophilicity, and can form stable salt compounds with a variety of metal ions. These salt compounds are easy to dissolve in solution, and show good nucleation and growth characteristics during crystal growth, which are suitable for growing high-quality optical crystals by solution method. However, there are few types of methanesulfonate compounds at present, which are difficult to apply to different fields. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a compound, the chemical formula of the compound is M y (SO3CH3)X·nH2O;

[0004] Wherein, M is Sr or Ba; X is Cl, Br or I; n is 2 or 4, and y is 1 or 2.

[0005] The present invention also provides the chemical formula M y A method for preparing a compound of (SO3CH3)X·nH2O, the method comprising:

[0006] The compound containing the element M, the compound containing the element X and the compound containing the methylsulfonic acid group are mixed and subjected to a hydrothermal reaction to prepare the compound having the chemical formula M y Compound of (SO3CH3)X·nH2O.

[0007] According to an embodiment of the present invention, the compound containing the M element is selected from at least one of M(OH)2·nH2O, MO, MF2, MCl2·nH2O, MBr2, M(NO3)2, MC2O2, MCO3, M(HCO3)2, and MSO4. For example, the compound containing the M element is selected from at least one of Sr(OH)2·nH2O (for example, Sr(OH)2·8H2O), SrO, SrF2, SrCl2·nH2O, SrCl2, SrBr2, Sr(NO3)2, SrC2O2, SrCO3, Sr(HCO3)2, SrSO4, Ba(OH)2·nH2O (for example, Ba(OH)2·8H2O), BaO, BaF2, BaCl2·nH2O, BaBr2, Ba(NO3)2, BaC2O2, BaCO3, Ba(HCO3)2, and BaSO4.

[0008] According to an embodiment of the present invention, the compound containing the element X is selected from RX2, NH4X, NH4HX, AX, wherein A is Li, Na, K, Rb or Cs, R is Ca, Sr or Ba; and X is at least one of Cl, Br or I. For example, SrCl2, BaCl2, NH4Cl, NH4Br or NH4I.

[0009] According to an embodiment of the present invention, the compound containing a methylsulfonic acid group is selected from SO3CH4, ASO3CH3, R(CH4SO3)2, wherein A is at least one of Li, Na, K, Rb or Cs; R is at least one of Ca, Sr or Ba, preferably SO3CH4. When the compound containing the M element and the compound containing the X element are both selected from RX2, wherein R is Sr or Ba, the addition amount is calculated according to the stoichiometric ratio in the chemical formula, or the addition amount is determined according to the following ratio.

[0010] According to an embodiment of the present invention, in the compound containing a methylsulfonic acid group, the compound containing an X element, and the compound containing an M element, the molar ratio of methylsulfonic acid, X, and M is (1-6):(1-6):(1-6); preferably (1-3):(1-3):(1-3); exemplified by 1:1:3, 1:1:1, and 3:1:1.

[0011] According to an embodiment of the present invention, the hydrothermal reaction is carried out in a solvent, and the solvent may be selected from an inorganic solvent, such as water, exemplified by deionized water.

[0012] According to an embodiment of the present invention, the volume ratio of the sum of the masses of the compound containing the X element, the compound containing the M element, and the compound containing the methylsulfonic acid group to the solvent can be (1.5-6.5) g:10 mL, preferably (2.5-5) g:10 mL; exemplified by 2.5 g:10 mL.

[0013] According to an embodiment of the present invention, the reaction temperature of the hydrothermal reaction may be 90 to 220° C., preferably 180 to 220° C., for example 180° C., 200° C., 220° C. Further, the heating rate of the hydrothermal reaction may be 10 to 30° C. / h, exemplified by 10° C. / h, 20° C. / h, 30° C. / h.

[0014] According to an embodiment of the present invention, the reaction time of the hydrothermal reaction may be 1 to 5 days, preferably 3 to 4 days, exemplified by 3 days and 4 days.

[0015] According to an embodiment of the present invention, the preparation method further comprises: after the hydrothermal reaction is completed, the temperature is lowered to room temperature at a rate of 10-20°C / h, and the compound is evaporated from the reaction solution at 40-60°C.

[0016] The present invention also provides a crystal, the chemical formula of which is M y (SO3CH3)X·nH2O, that is, the crystal is M y (SO3CH3)X·nH2O crystal.

[0017] According to an embodiment of the present invention, the crystal is Sr(SO3CH3)Cl·4H2O crystal, which belongs to the monoclinic system, has a symmetry center, and a space group of P21 / n. α=γ=90°, β=105.585(6)°, Z=4.

[0018] According to an embodiment of the present invention, the crystal is Sr(SO3CH3)Br·4H2O crystal, which belongs to the orthorhombic system, has a symmetry center, and a space group of Pnma. α=β=γ=90°, Z=8.

[0019] According to an embodiment of the present invention, the crystal is Sr(SO3CH3)I·4H2O crystal, which belongs to the tetragonal system, has a symmetry center, and a space group of P4 / nmm. α=γ=90°, β=109.916(4)°, Z=4.

[0020] According to an embodiment of the present invention, the crystal is Ba(SO3CH3)Cl·4H2O crystal, which belongs to the tetragonal system, has a symmetry center, and a space group of P4 / nmm. α=β=γ=90°, Z=2.

[0021] According to an embodiment of the present invention, the crystal is Ba(SO3CH3)Br·4H2O crystal, which belongs to the monoclinic system, has a symmetry center, and a space group of P21 / n. α=β=γ=90°, Z=2.

[0022] According to an embodiment of the present invention, the crystal is Ba(SO3CH3)I·2H2O crystal, which belongs to the orthorhombic system, has a symmetry center, and a space group of Pbca. α=β=γ=90°, Z=8.

[0023] According to an embodiment of the present invention, the crystal is Ba2(SO3CH3)3I·4H2O crystal, which belongs to the triclinic system, has a symmetry center, and a space group of α=90.3110(10)°, β=92.8880(10)°, γ=113.2650(10)°, Z=4.

[0024] According to an embodiment of the present invention, the crystal has Figure 1 The crystal structure is shown.

[0025] According to an embodiment of the present invention, the crystal is formed by connecting M atoms and SO3CH3 through shared O atoms to form a two-dimensional infinite M-SO3CH3 layer, and the halogen X is between the two layers.

[0026] According to an embodiment of the present invention, the Sr(CH3SO3)Cl·4H2O crystal has the following characteristics: Figure 2 X-ray diffraction pattern shown.

[0027] According to an embodiment of the present invention, the ultraviolet absorption edges of the crystals can reach 183 and 184 nm respectively.

[0028] The present invention also provides a method for preparing the crystal, characterized in that the method comprises:

[0029] The compound containing the X element, the compound containing the M element and the compound containing the methylsulfonic acid group are mixed and heated for crystallization to obtain the crystal.

[0030] Preferably, the compound containing the X element, the compound containing the M element and the compound containing the methylsulfonic acid group are selected from the above chemical formula M y The selection in the preparation method of the compound (SO3CH3)X·nH2O is consistent.

[0031] According to an embodiment of the present invention, the method is carried out in a solvent. The solvent has the meaning as described above.

[0032] According to an embodiment of the present invention, the temperature of the heating crystallization is 180 to 220°C;

[0033] The heating crystallization time is 1 to 15 days, preferably 2 to 5 days, and exemplified by 2 days, 3 days, 4 days or 5 days.

[0034] According to an embodiment of the present invention, the method for preparing the crystal further comprises: after the reaction is completed, cooling to room temperature at a rate of 1 to 10°C / h, and evaporating the crystal at 20-40°C.

[0035] According to an embodiment of the present invention, the method for preparing the crystal specifically comprises the following steps:

[0036] (1) mixing a compound containing an X element, a compound containing an M element, a compound containing methanesulfonic acid, and a solvent, heating the mixture to 180 to 220° C. at a rate of 10 to 30° C. / h for crystallization for 1 to 15 days;

[0037] (2) After the reaction, the reaction solution is cooled to room temperature at a rate of 1-10°C / h, and the crystals are evaporated at 20-40°C.

[0038] The present invention also provides application of the crystal in the field of photorefractive information processing or as a chemical raw material.

[0039] Beneficial effects of the present invention:

[0040] The inventors have found that methanesulfonate compounds have gradually become a hot topic in optical material research in recent years due to their unique molecular structure and chemical stability. Methanesulfonate crystals have a wide light transmittance range and good thermal stability, and are easy to grow by solution method, suitable for large-scale production. Specifically, the crystals of the present application have the following characteristics:

[0041] (1) The present invention provides a novel halogen-containing methanesulfonic acid alkaline earth metal salt compound and its crystal, wherein the crystal is crystallized in a centrosymmetric space group P21 / n, Pnma, P4 / nmm, P4 / nmm, P21 / n, Pbca or Its structural feature is that the alkaline earth metal atom M and SO3CH3 are connected by a shared O atom to form a two-dimensional infinite alkaline earth metal M-SO3CH3 layer, and the halogen is between the two layers. The introduction of halogen improves the system of metal methyl sulfonate. At the same time, the crystal of this system does not absorb moisture, is stable in air, and has good physical properties.

[0042] (2) The physical and chemical properties of the crystals of the present invention are stable.

[0043] (3) The preparation method of the compound and crystal of the present invention has a simple process, a fast growth rate and a low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic diagram of the crystal structure of the Sr(SO3CH3)Cl·4H2O crystal of the present invention.

[0045] Figure 2 The X-ray diffraction pattern obtained by fitting the crystal structure of the Sr(SO3CH3)Cl·4H2O crystal of Example 2-1 is compared with the X-ray diffraction of the sample powder in Example 1. DETAILED DESCRIPTION

[0046] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0047] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0048] Example 1

[0049] Preparation of Sr(SO3CH3)Cl·4H2O compound:

[0050] (a) SrCl2 (2.378 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was increased to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0051] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 10-20°C / h, and Sr(SO3CH3)Cl·4H2O compound is obtained after evaporation at 40-60°C.

[0052] Preparation of Sr(SO3CH3)Br·4H2O compound:

[0053] (a) Sr(OH)2·8H2O (1.329 g), NH4Br (0.490 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0054] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 10-20°C / h, and Sr(SO3CH3)Br·4H2O compound is obtained after evaporation at 40-60°C.

[0055] The preparation of Sr(SO3CH3)I·4H2O compound only needs to replace the corresponding raw materials in the preparation of Ba(SO3CH3)Br·4H2O. For example, to prepare Sr(SO3CH3)I·4H2O, the raw material NH4I can be used to replace NH4Br. Preparation of Ba(SO3CH3)I·2H2O compound

[0056] (a) Ba(OH)2·8H2O (1.329 g), NH4I (2.174 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0057] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 10-20°C / h, and Ba(SO3CH3)I·2H2O compound is obtained after evaporation at 40-60°C.

[0058] Preparation of Ba2(SO3CH3)3I·4H2O Compound

[0059] (a) Ba(OH)2·8H2O (1.329 g), NH4I (0.725 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0060] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 10-20°C / h, and after evaporation at 40-60°C, Ba2(SO3CH3)3I·4H2O compound can be obtained.

[0061] The preparation of Ba(SO3CH3)Cl·4H2O and Ba(SO3CH3)Br·4H2O compounds only requires replacing the corresponding raw materials in the preparation of Ba(SO3CH3)I·4H2O. For example, to prepare Br(SO3CH3)Br·4H2O, the raw material NH4Br can be used to replace NH4I.

[0062] Example 2-1

[0063] Preparation of Sr(SO3CH3)Cl·4H2O crystals:

[0064] (a) SrCl2 (2.378 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was increased to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0065] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 10°C / h, and Sr(SO3CH3)Cl·4H2O crystals are obtained after evaporation at 20-40°C.

[0066] Preparation of Sr(SO3CH3)Br·4H2O crystals:

[0067] (a) Sr(OH)2·8H2O (1.329 g), NH4Br (0.490 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0068] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 10°C / h, and Sr(SO3CH3)Br·4H2O crystals are obtained after evaporation at 20-40°C.

[0069] The preparation of Sr(SO3CH3)I·4H2O crystals only requires replacing the corresponding raw materials in the preparation of Ba(SO3CH3)Br·4H2O crystals. For example, to prepare Sr(SO3CH3)I·4H2O crystals, the raw material NH4I can be used to replace NH4Br. Preparation of Ba(SO3CH3)I·2H2O crystals

[0070] (a) Ba(OH)2·8H2O (1.329 g), NH4I (2.174 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0071] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 10°C / h, and Ba(SO3CH3)I·2H2O crystals are obtained after evaporation at 20-40°C.

[0072] Preparation of Ba2(SO3CH3)3I·4H2O Crystal

[0073] (a) Ba(OH)2·8H2O (1.329 g), NH4I (0.725 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0074] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 10°C / h, and Ba2(SO3CH3)3I·4H2O crystals can be obtained after evaporation at 20-40°C.

[0075] The structural diagram of the Sr(SO3CH3)Cl·4H2O crystal prepared in this embodiment is shown in FIG. Figure 1 As shown, the unit cell parameters are: Sr(SO3CH3)Cl·4H2O crystal: monoclinic system, with a symmetry center, space group P21 / n, α=γ=90°, β=105.585(6)°, Z=4.

[0076] Example 2-2

[0077] Preparation of Sr(SO3CH3)Br·4H2O crystals:

[0078] (a) Sr(OH)2·8H2O (1.329 g), NH4Br (0.490 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0079] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 10°C / h, and Sr(SO3CH3)Br·4H2O crystals are obtained after evaporation at 20-40°C.

[0080] The prepared Sr(SO3CH3)Br·4H2O crystal is an orthorhombic crystal with a symmetry center and a space group of Pnma. α=β=γ=90°, Z=8.

[0081] Example 2-3

[0082] The difference between Example 2-3 and Example 2-2 is that the raw material NH4I is used to replace NH4Br.

[0083] The prepared Sr(SO3CH3)I·4H2O crystal is a tetragonal crystal with a symmetry center and a space group of P4 / nmm. α=γ=90°, β=109.916(4)°, Z=4.

[0084] Embodiment 2-4

[0085] The difference between Example 2-4 and Example 2-2 is that Ba(OH)2·8H2O is used to replace Sr(OH)2·8H2O, and NH4Cl is used to replace NH4Br.

[0086] The prepared Ba(SO3CH3)Cl·4H2O crystals are tetragonal with a symmetry center and a space group of P4 / nmm. α=β=γ=90°, Z=2.

[0087] Embodiment 2-5

[0088] The difference between Example 2-5 and Example 2-2 is that Ba(OH)2·8H2O is used to replace Sr(OH)2·8H2O.

[0089] The prepared Ba(SO3CH3)Br·4H2O crystal is a monoclinic crystal with a symmetry center and a space group of P21 / n. α=β=γ=90°, Z=2.

[0090] Embodiment 2-6

[0091] Preparation of Ba(SO3CH3)I·2H2O Crystals

[0092] (a) Ba(OH)2·8H2O (1.329 g), NH4I (2.174 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0093] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 10°C / h, and Ba(SO3CH3)I·2H2O crystals are obtained after evaporation at 20-40°C.

[0094] The prepared Ba(SO3CH3)I·2H2O crystal is an orthorhombic crystal with a symmetry center and a space group of Pbca. α=β=γ=90°, Z=8.

[0095] Embodiment 2-7

[0096] Preparation of Ba2(SO3CH3)3I·4H2O Crystal

[0097] (a) Ba(OH)2·8H2O (1.329 g), NH4I (0.725 g), SO3CH4 (0.481 g) and 10 mL of water were mixed and placed in a reactor with a polytetrafluoroethylene liner (25 mL). The temperature was raised to 180 °C at a rate of 20 °C / h and kept constant for 2 days.

[0098] (b) After the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 10°C / h, and Ba2(SO3CH3)3I·4H2O crystals are obtained after evaporation at 20-40°C.

[0099] The prepared Ba2(SO3CH3)3I·4H2O crystal is a triclinic system with a symmetry center and a space group of α=90.3110(10)°, β=92.8880(10)°, γ=113.2650(10)°, Z=4.

[0100] Example 3

[0101] Structural analysis and phase analysis of crystals of Examples 2-1 to 2-7

[0102] The crystal samples prepared in Examples 2-1 to 2-7 were analyzed by single crystal X-ray diffraction. The crystal structures of Examples 2-1 to 2-7 were analyzed by using a Bruker SMART APEXⅢCCD diffractometer with a single crystal X-ray diffraction device and Mo Kα radiation. The data were recorded at 293(2)K with a scan mode of ω = 2θ. The data were processed for absorption correction using the Multi-Scan method. The structure was solved using the SHELXTL package; the positions of heavy atoms were determined by direct methods, and the coordinates of the remaining atoms were obtained by difference Fourier synthesis; the F-based 2 The full matrix least squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters. The chemical formulas of the crystals obtained in Examples 2-1 to 2-7 are Sr(SO3CH3)Cl·4H2O, Sr(SO3CH3)Br·4H2O, Sr(SO3CH3)I·4H2O, Ba(SO3CH3)Cl·4H2O, Ba(SO3CH3)Br·4H2O, Ba(SO3CH3)I·2H2O and Ba2(SO3CH3)3I·4H2O, respectively.

[0103] The phases prepared in Examples 1-2 were analyzed by powder X-ray diffraction. Powder X-ray diffraction (XRD) data of each compound in Example 1 and the crystal in Example 2 were collected on a SmartLab9KW powder X-ray diffractometer with Cu-Kα radiation in the range of 5° to 70° (2θ), with a step width of 0.01° and a step length of 2s. The powder X-ray diffraction data showed that the diffraction peak positions of the samples in Examples 1 to 3 were basically the same.

[0104] like Figure 2 As shown, the X-ray diffraction pattern obtained by fitting the crystal structure of the Sr(SO3CH3)Cl·4H2O crystal of Example 2-1 is basically consistent with the peak position and intensity of the X-ray diffraction pattern of the sample powder of Example 1. This shows that the single crystal prepared in Example 2-1 of the present invention is a single pure phase with high purity.

[0105] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A compound, characterized in that The chemical formula of the compound is M y (SO3CH3)X·nH2O; Wherein, M is Sr or Ba; X is Cl, Br or I; n is 2 or 4, and y is 1 or 2.

2. The method for preparing the compound according to claim 1, characterized in that: The method is: The compound containing the element M, the compound containing the element X and the compound containing the methylsulfonic acid group are mixed and subjected to a hydrothermal reaction to prepare the compound having the chemical formula M y Compound of (SO3CH3)X·nH2O.

3. The method according to claim 2, characterized in that The compound containing the M element is selected from at least one of M(OH)2·nH2O, MO, MF2, MCl2·nH2O, MBr2, M(NO3)2, MC2O2, MCO3, M(HCO3)2, and MSO4. For example, the compound containing the M element is selected from at least one of Sr(OH)2·nH2O, SrO, SrF2, SrCl2·nH2O, SrCl2, SrBr2, Sr(NO3)2, SrC2O2, SrCO3, Sr(HCO3)2, SrSO4, Ba(OH)2·nH2O, BaO, BaF2, BaCl2·nH2O, BaBr2, Ba(NO3)2, BaC2O2, BaCO3, Ba(HCO3)2, and BaSO4.

4. The method according to claim 2, characterized in that: The compound containing the element X is selected from RX2, NH4X, NH4HX, AX, wherein A is Li, Na, K, Rb or Cs, R is Ca, Sr or Ba, and X is at least one of Cl, Br or I. For example, SrCl2, BaCl2, NH4Cl, NH4Br or NH4I. Preferably, the methylsulfonic acid group-containing compound is selected from SO3CH4, ASO3CH3, R(CH4SO3)2, wherein A is at least one of Li, Na, K, Rb or Cs; and R is at least one of Ca, Sr or Ba. Preferably, in the compound containing a methylsulfonic acid group, the compound containing an X element, and the compound containing an M element, the molar ratio of methylsulfonic acid, X, and M is (1-6):(1-6):(1-6).

5. The method according to claim 2, characterized in that: The hydrothermal reaction is carried out in a solvent, and the solvent is selected from an inorganic solvent. Preferably, the reaction temperature of the hydrothermal reaction is 90 to 220° C.; and the reaction time of the hydrothermal reaction is 1 to 5 days.

6. A crystal, characterized in that: The chemical formula of the crystal is M shown in claim 1 y (SO3CH3)X·nH2O, that is, the crystal is M y (SO3CH3)X·nH2O crystal.

7. The crystal according to claim 6, characterized in that The crystal is Sr(SO3CH3)Cl·4H2O crystal, belongs to the monoclinic system, has a symmetry center, and a space group of P21 / n. α=γ=90°, β=105.585(6)°, Z=4; Alternatively, the crystal is Sr(SO3CH3)Br·4H2O crystal, which belongs to the orthorhombic system, has a symmetry center, and a space group of Pnma. α=β=γ=90°, Z=8; Alternatively, the crystal is Sr(SO3CH3)I·4H2O crystal, which belongs to the tetragonal system, has a symmetry center, and a space group of P4 / nmm. α=γ=90°, β=109.916(4)°, Z=4; Alternatively, the crystal is Ba(SO3CH3)Cl·4H2O crystal, which belongs to the tetragonal system, has a symmetry center, and a space group of P4 / nmm. α=β=γ=90°, Z=2; Alternatively, the crystal is Ba(SO3CH3)Br·4H2O crystal, which belongs to the monoclinic system, has a symmetry center, and a space group of P21 / n. α=β=γ=90°, Z=2; Alternatively, the crystal is Ba(SO3CH3)I·2H2O crystal, which belongs to the orthorhombic system, has a symmetry center, and a space group of Pbca. α=β=γ=90°, Z=8; Alternatively, the crystal is Ba2(SO3CH3)3I·4H2O crystal, which belongs to the triclinic system, has a symmetry center, and a space group of α=90.3110(10)°, β=92.8880(10)°, γ=113.2650(10)°, Z=4.

8. The crystal according to claim 6, characterized in that The crystal is composed of M atoms and SO3CH3 connected by shared O atoms to form a two-dimensional infinite M-SO3CH3 layer, and the halogen X is between the two layers.

9. The method for preparing the crystal according to any one of claims 6 to 8, characterized in that: The method is: The compound containing the X element, the compound containing the M element and the compound containing the methylsulfonic acid group are mixed and heated for crystallization to obtain the crystal. Preferably, the temperature of the heating crystallization is 180-220° C.; and the time of the heating crystallization is 1-15 days.

10. Use of the crystal according to any one of claims 6 to 8 in the field of photorefractive information processing or as a chemical raw material.

Citation Information

Patent Citations

  • High yield and rapid synthesis method for processing organic metal salt

    CN101010087A

  • Sulfur-based electrolyte solution for magnesium cell

    CN113166043A

  • Nonlinear optical crystal barium methanesulfonate as well as preparation method and application thereof

    CN116446051A

  • Series of compound methane sulfonate, methane sulfonate nonlinear optical crystal, and preparation method and application of methane sulfonate nonlinear optical crystal

    CN117567327A